AFRICAN YOUTH: Stimulus and brake to the effective implementation of the African Continental Free Trade Area - (:unkn) unknown (My University, 2021)
This paper proposes to explain why African youth can be both an "opportunity" (asset) and a "risk" (problem) in the implementation of the African Continental Free Trade Area (AfCFTA). The paper begins by defining the theoretical framework of the analysis. It then presents the demographic trends in Africa to illustrate the place of African youth in the paradigmatic renewal of the continent. From these trends, it makes two fundamental arguments justifying the interest of relying on African youth in order to capitalize on the gains of the AfCFTA. Finally, this paper considers that relying on youth for effective implementation of the AfCFTA is of undeniable importance for two reasons: (1) Because youth are a catalyst for the future progress of the continent. (2) Because youth can be a liability if nothing is done to address unemployment; boost quality job creation; change the youth training paradigm; and promote STEM (Science, Technology, Engineering and Math).
Keywords: African Research